Community Engagement and Readiness for E-waste Initiatives: Attitudes, Barriers and Opportunities - Hossain, Irin; Rahman, Md Shafiur; Abbas, Md Golam; Sattar, Shahria; Nazneen, Afsana (Medicine Today, 2025)
Introduction: The research "Community Engagement and Readiness for E-waste Initiatives: Attitudes, Barriers, and Opportunities" investigates the attitudes, barriers, and opportunities regarding e-waste management among community members in four divisional cities of Bangladesh. Materials and Methods: A cross-sectional design was employed over six months from January to June 2024, focusing on community members in Dhaka, Chittagong, Rajshahi, and Khulna. A stratified random sampling technique selected 408 participants based on their involvement with e-waste and willingness to participate. Data were collected using a semi-structured questionnaire. Results: Participants included 58.8% males and 41.2% females, with the majority aged between 20-30 years. Education levels varied, with 14.5% holding a Bachelor's degree, while 23.5% were classified as illiterate or with minimal education. Most participants lived in urban areas (69.4%). Mobile phones were the most commonly used devices (99.3%), followed by televisions (73.8%), refrigerators (56.9%), and laptops/computers/tablets (17.2%). Recycling was the most common e-waste disposal method (47.3%), with 63% selling old devices. Environmental concern motivated 28% to recycle, while personal values motivated 40.4%. Social media was the most common source of information regarding e-waste disposal (33.8%). The government was perceived as primarily responsible for e-waste recycling (68.4%). A lack of convenient recycling facilities was identified as the most significant barrier (13.5%) hindering participation in e-waste initiatives. Regarding information on e-waste recycling options, 57.8% agreed, with 29.2% strongly agreeing. In believing that e-waste recycling reduces environmental impact, 75.7% agreed, with 25.5% strongly agreeing. Cancer was identified as the most prevalent health concern (28.9%), followed by respiratory problems (25.7%) and skin problems (22.5%). Conclusion: While there is a general awareness of the importance of e-waste recycling, significant barriers such as a lack of facilities and information hinder effective participation. To improve community engagement, efforts should focus on enhancing public awareness, improving infrastructure, and incorporating schools and digital platforms into the solution. Medicine Today 2025, Vol.37 (1): 102-107